Distance and Bandwidth Estimation for MIMO Channel - Rusko, A.; Novikovs, V.; Balodis, G. (Elektronika ir Elektrotechnika, 2007)
We presented the distance and bandwidth estimation measurements for fixed environment multiple-input-multiple-output (MIMO) wideband radio channel, based on orthogonal frequency-division-multiplexing (OFDM). Channel capacity measurements experiment have been carried out in an indoor line-of-sight (LOS) and non-line-of-sight (NLOS) corridor environment. Channel bandwidth were measured systematically with lineary varying distance in a static indoor environment. Measurements have shown that in the indoor LOS and NLOS environment MIMO systems have achieved sufficiently higher channel capacity because the MIMO channel is more robust to correlation when the signal-to-noise-ratio (SNR) is high. Influence of antenna polarisation was taken in fact. Measurements were also taken in anechoic chamber, to realise higher SNR. Ill. 6, bibl. 8 (in English; summaries in English, Russian and Lithuanian).